2009
DOI: 10.1038/pcan.2009.37
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dutasteride, tamsulosin, and the combination on storage and voiding in men with benign prostatic hyperplasia and prostatic enlargement: 2-year results from the Combination of Avodart and Tamsulosin study

Abstract: This article reports the results of a post hoc analysis of the multicenter, randomized, double-blind Combination of Avodart and Tamsulosin (CombAT) study, which aimed to investigate the effects of dutasteride (0.5 mg), tamsulosin (0.4 mg), and their combination on storage and voiding symptoms in 4844 men aged X50 years with moderate-to-severe lower urinary tract symptoms (International Prostate Symptom Score X12), prostate volume (PV) X30 cm 3 and PSA 1.5-10 ng ml À1. After 24 months, combination treatment ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 25 publications
5
29
2
Order By: Relevance
“…Another hypothesis is that the bladder outlet resistance is decreased if the size of the enlarged prostate, which mechanically obstructs the bladder outlet, is decreased in patients with BPH, thus leading to an improvement in storage symptoms. On the basis of this concept, Becher et al [17] reported that storage symptoms were improved with the use of dutasteride, a type of 5 ARI, alone, and that in the dutasteride and tamsulosin combination treatment group, as compared with the monotherapy group, the storage and voiding subscores were significantly decreased. In addition, the voiding subscore was further decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is that the bladder outlet resistance is decreased if the size of the enlarged prostate, which mechanically obstructs the bladder outlet, is decreased in patients with BPH, thus leading to an improvement in storage symptoms. On the basis of this concept, Becher et al [17] reported that storage symptoms were improved with the use of dutasteride, a type of 5 ARI, alone, and that in the dutasteride and tamsulosin combination treatment group, as compared with the monotherapy group, the storage and voiding subscores were significantly decreased. In addition, the voiding subscore was further decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Patients being treated with combination therapy experienced a similar reduction in risk of developing acute urinary retention or requiring BPH‐related surgery to that of patients treated with finasteride alone 17 . The Combination of Avodart and Tamsulosin (CombAT) study was the most extensive trial evaluating the efficacy of combination therapy in patients with moderate‐to‐severe LUTS/BPH and enlarged prostates (more than 30 mL) 18 . Combination therapy was shown to lead to greater reductions in storage subscores than dutasteride monotherapy and tamsulosin monotherapy from months 3 and 12, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy was also more effective than either monotherapy for improvement of voiding symptoms in patients with a prostate volume of 30–42 mL 39. The authors also showed that combination therapy was associated with significantly greater improvement in patient-reported disease-specific quality of life and treatment satisfaction than both monotherapies after treatment for 2 years 4…”
Section: Combination Therapymentioning
confidence: 92%